PERAN SEKRETARIS DALAM MENGATUR SEGALA PERSIAPAN PERJALANAN BISNIS PIMPINAN PADA CV. PUTERA PRATAMA - Yulia Mujiaty; Siti Nurjanah (Jurnal Akrab Juara, 2018)
As a secretary of knowledge and skills that need to be owned one of them is the setting of official travel or business trip leadership. He must know the rules of all types of transportation, how the procedures, services and contact travel agents or travel bureau with ease. To improve relationships and develop script or productivity expansion. So a leader often travel business outside the city and even abroad. In this case the leader needs a secretary to organize everything related to his journey. Keywords: The Role of the Secretary Manages all the Preparation of the Leadership Business Journey.